Diagnostic algorithm of magnifying endoscopy with crystal violet staining for non‐ampullary duodenal epithelial tumors. Issue 7 (25th February 2020) - Toya, Yosuke; Endo, Masaki; Oizumi, Tomofumi; Akasaka, Risaburo; Yanai, Shunichi; Kawasaki, Keisuke; Nakamura, Shotaro; Eizuka, Makoto; Fujita, Yasuko; Uesugi, Noriyuki; Ishida, Kazuyuki; Sugai, Tamotsu; et al.
Abstract : Objectives: Little is known about the usefulness of magnifying endoscopy with crystal violet staining (ME‐CV) for the diagnosis of duodenal tumors. We assessed the ability of ME‐CV to distinguish Vienna classification (VCL) category 4/5 (C4/5) from category 3 (C3) non‐ampullary duodenal epithelial tumors (NADETs). Methods: A total of 76 NADETs were studied. We retrospectively analyzed the diagnostic values of the white light endoscopy (WLE) scoring system and the ME‐CV algorithm with receiver operating characteristic (ROC) curves, and three endoscopists calculated the sensitivity, specificity, accuracy, and the area under the curve (AUC) of each. The diagnostic values were tested among NADETs overall and among subgroups of tumors with gastric, gastrointestinal or intestinal mucin phenotypes. Inter‐observer agreement of the diagnostic results was also calculated. Results: According to the VCL, 54 lesions (71.1%) were regarded as C3 and 22 lesions (28.9%) as C4/5. The sensitivity, specificity, accuracy and AUC of ME‐CV were higher than those of the WLE scoring system (63.6 vs 54.5, 85.2 vs 75.9, 78.9 vs 69.7, 0.744 vs 0.652, respectively). Inter‐observer agreements of the WLE scoring system and ME‐CV were both moderate (kappa 0.45 and 0.41). ME‐CV had higher sensitivity, specificity, accuracy and AUC than those of the WLE scoring system among the gastric and intestinal phenotypes of NADETs. Conclusions: ME‐CV is appropriate for the diagnosis of C4/5 and C3 NADETs.